GENDER REPRESENTATION IN INDONESIAN EFL HIGH SCHOOL TEXTBOOK THROUGH CONVERSATION TEXTS - Mullynanda Pontiaka (TLEMC (Teaching and Learning English in Multicultural Contexts), 2019)
Gender representation in schools is one such field of ELT study. Since students spend most of their time at school, gender representation could affect students’ language use and social life. Half of the influence comes from the material they learn; it is a textbook. A textbook is a crucial device to deliver language and social behavior. Asking male to start the discussion, and the female has less portion in two ways communication are the acts of gender stereotyping in language. The concern about it is an up-bringing judgment through social behavior. Otherwise, the textbook is not a single-handed influence because students' attitude in social life matters. The need for students' awareness of avoiding gender bias sets this article. Another objective is to reveal how gender role represented in conversation tasks of high school English textbook. This investigation also examines gender-neutral and gender-marked constructions used in conversation texts. The researcher undertakes a content analysis in a textbook with a qualitative research method. The researcher decides it is a content analysis research design. Afterward, the researcher concludes that gender role in conversation texts of English textbook is fairly represented and the English textbook has progressive content. As the example is the appearance number between men and women is equal. Through this research, the researcher expects that education practitioners (students; teacher) understand non-gendered/gendered-words and practice conversation without stereotyping gender role textually and socially.